A negative electrode sheet, a battery assembly, a battery, and an electric device
Patent Information
- Application Number
- CN202521416745.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Utility models(China)
- Current Assignee / Owner
- Filing Date
- 2025-07-07
- Publication Date
- 2026-10-27
- Estimated Expiration
- 2035-07-07
AI Technical Summary
[0004]有鉴于此,本公开致力于提供一种负极极片、电池组件、电池和用电装置,以解决现有技术中锂离子电池中高能量密度和高功率特性难以同时兼容的问题
[0025]通过上述技术方案,本公开的有益技术效果为:本公开在负极极片上直接设置孔通道阵列,可以降低负极极片的孔隙迂曲度,能够实现对多层活性物质结构中孔道阵列的精确控制,不仅增强了活性物质层之间的结合力,还通过引入额外的通道结构,提高了极片的整体结构稳定性。同时,通过调控极片多孔结构的梯度分布,可以实现上层高孔隙率结构,下层高压实密度结构,这种结构既保证了高能量密度,又兼顾了快充性能。
Smart Images

Figure CN224907976U_ABST
Abstract
Description
Technical Field
[0001] This disclosure relates to the field of battery technology, and more specifically, to a negative electrode, a battery assembly, a battery, and an electrical device. Background Technology
[0002] Currently, the defects of graphite materials in applications are becoming increasingly significant, becoming one of the constraints limiting the performance of lithium-ion batteries. For example, the regular layered structure and high anisotropy of natural graphite result in slow lithium-ion insertion, severely limiting its rate performance. Furthermore, uneven surface reactions also lead to uneven film formation on the electrode surface. While synthetic graphite exhibits better cycle performance and high charge-discharge efficiency, its manufacturing process is complex, its cost is relatively high, and its energy density is lower. The conventional single-graphite anode structure limits the effective balance between high-current charge-discharge capability and cycle charge-discharge capability in lithium-ion batteries, making it difficult to meet the application requirements of high energy density and high power characteristics.
[0003] Therefore, there is an urgent need to develop and design a composite negative electrode with a hierarchical structure that combines excellent properties such as high adhesion to current collectors, small volume change, and high ionic and electronic conductivity. This can significantly enhance the fast charging capability of lithium-ion batteries and meet the requirements of lithium-ion batteries for both high energy density and high power characteristics. Utility Model Content
[0004] In view of this, this disclosure aims to provide a negative electrode sheet, a battery assembly, a battery, and an electrical device to solve the problem that high energy density and high power characteristics are difficult to simultaneously achieve in existing lithium-ion batteries.
[0005] To solve the above-mentioned technical problems, this disclosure is implemented as follows:
[0006] The first aspect of this disclosure provides a negative electrode sheet, the negative electrode sheet comprising a negative current collector, a first active material layer disposed on at least one side surface of the negative current collector along the thickness direction, a second active material layer disposed on one side surface of the first active material layer away from the negative current collector, and a third active material layer disposed on one side surface of the second active material layer away from the first active material layer.
[0007] The negative electrode sheet is provided with a pore channel array from the surface of the third active material layer to the surface of the negative electrode current collector;
[0008] The aperture array includes a first through hole, a second through hole, and a third through hole;
[0009] The first through hole penetrates the third active material layer, the second active material layer and the first active material layer; the second through hole penetrates the third active material layer and the second active material layer; and the third through hole penetrates the third active material layer.
[0010] Optionally, the negative electrode includes one or more of the following features (1) to (6):
[0011] (1) The diameter of the first through hole is 10 to 50 μm;
[0012] (2) The diameter of the second through hole is 10 to 50 μm;
[0013] (3) The diameter of the third through hole is 10 to 50 μm;
[0014] (4) The pore spacing L1 in the first active material layer satisfies the following relationship: 60≤L1≤100μm; the porosity of the first active material layer is 5~25%;
[0015] (5) The pore spacing L2 in the second active material layer satisfies the following relationship: 30≤L2<60μm, and the porosity of the second active material layer is 30~55%;
[0016] (6) The pore spacing L3 in the third active material layer satisfies the following relationship: 10≤L3<30μm, and the porosity of the third active material layer is 70~90%.
[0017] Optionally, the thickness of the first active material layer is 30–70 μm; and / or, the thickness of the second active material layer is 110–250 μm; and / or, the thickness of the third active material layer is 30–70 μm.
[0018] Optionally, the first active material layer includes a first active material, which is artificial graphite; and / or, the second active material layer includes a second active material, which is artificial graphite; and / or, the third active material layer includes a third active material, which includes natural graphite and / or hard carbon.
[0019] Optionally, the pore channel array is distributed in a vertical array on the surface of the third active material layer; or, the pore channel array is distributed in a ring array on the surface of the third active material layer.
[0020] Optionally, the negative electrode sheet may further include a protective layer disposed on the side surface of the third active material layer away from the second active material layer.
[0021] Optionally, the thickness of the protective layer is 30–70 μm; and / or, the protective layer includes a solid electrolyte, wherein the solid electrolyte includes at least one of a sulfide electrolyte, an oxide electrolyte, a polymer electrolyte, and a ceramic electrolyte.
[0022] A second aspect of this disclosure provides a battery assembly including a negative electrode sheet, wherein the negative electrode sheet is the aforementioned negative electrode sheet.
[0023] A third aspect of this disclosure provides a battery comprising a negative electrode plate, wherein the negative electrode plate is the negative electrode plate described above.
[0024] A fourth aspect of this disclosure provides an electrical device comprising a battery, wherein the battery is the battery described above.
[0025] The beneficial technical effects of this disclosure through the above technical solution are as follows: This disclosure directly sets a pore channel array on the negative electrode sheet, which can reduce the porosity of the negative electrode sheet and achieve precise control over the pore array in the multi-layer active material structure. This not only enhances the bonding force between the active material layers but also improves the overall structural stability of the electrode sheet by introducing additional channel structures. Simultaneously, by controlling the gradient distribution of the porous structure of the electrode sheet, a high-porosity upper layer and a high-density lower layer can be achieved. This structure ensures both high energy density and fast-charging performance.
[0026] Other features and advantages of this disclosure will be described in detail in the following detailed description section. Attached Figure Description
[0027] The accompanying drawings are provided to further illustrate the present disclosure and form part of the specification. They are used together with the following detailed description to explain the present disclosure, but do not constitute a limitation thereof.
[0028] Figure 1 The diagram shown is a schematic of the negative electrode sheet of this disclosure.
[0029] Figure 2 The diagram shown is a schematic diagram of the channel distribution in Example 1.
[0030] Figure 3 The diagram shown is a schematic diagram of the channel distribution in Example 2. Detailed Implementation
[0031] This disclosure provides a negative electrode sheet, a battery assembly, a battery, and an electrical device. Those skilled in the art can refer to the content of this document and appropriately modify the process parameters to achieve the desired result. It should be particularly noted that all similar substitutions and modifications are obvious to those skilled in the art and are considered to be included in this disclosure. The methods and applications of this disclosure have been described through preferred embodiments. Those skilled in the art can clearly modify or appropriately change and combine the methods and applications described herein without departing from the content, spirit, and scope of this disclosure to implement and apply the technology of this disclosure.
[0032] In the description of this disclosure, the list of items connected by the term "at least one of" or other similar terms may mean any combination of the listed items. For example, if items A and B are listed, then the phrase "at least one of A and B" means only A; only B; or A and B. In another instance, if items A, B, and C are listed, then the phrase "at least one of A, B, and C" means only A; or only B; only C; A and B (excluding C); A and C (excluding B); B and C (excluding A); or all of A, B, and C. Item A may contain a single element or multiple elements. Item B may contain a single element or multiple elements. Item C may contain a single element or multiple elements.
[0033] The endpoints and any values of the ranges disclosed in this disclosure are not limited to the precise ranges or values, and such ranges or values should be understood to include values close to such ranges or values. For numerical ranges, the endpoint values of the various ranges, the endpoint values of the various ranges or individual point values, and individual point values can be combined with each other to obtain one or more new numerical ranges, which should be regarded as specifically disclosed in this disclosure.
[0034] Unless otherwise specified, all embodiments and optional embodiments of this disclosure can be combined to form new technical solutions.
[0035] Unless otherwise specified, all technical features and optional technical features of this disclosure can be combined to form new technical solutions.
[0036] Unless otherwise specified, the terms "comprising" and "including" as used in this disclosure can be open-ended or closed-ended. For example, "comprising" and "including" can mean that other components not listed may also be included, or that only the listed components may be included.
[0037] To address the challenge of simultaneously achieving high energy density and high power characteristics in existing lithium-ion batteries, this disclosure employs the following technical solution:
[0038] The first aspect of this disclosure provides a negative electrode plate, such as Figure 1As shown, the negative electrode sheet includes a negative current collector, a first active material layer disposed on at least one side surface of the negative current collector along the thickness direction, a second active material layer disposed on the side surface of the first active material layer away from the negative current collector, and a third active material layer disposed on the side surface of the second active material layer away from the first active material layer.
[0039] The negative electrode sheet is provided with a pore channel array from the surface of the third active material layer to the surface of the negative electrode current collector;
[0040] The aperture array includes a first through hole, a second through hole, and a third through hole;
[0041] The first through hole penetrates the third active material layer, the second active material layer and the first active material layer; the second through hole penetrates the third active material layer and the second active material layer; and the third through hole penetrates the third active material layer.
[0042] This disclosure discloses a method of directly incorporating a pore channel array on the negative electrode sheet, which reduces the porosity of the negative electrode sheet and enables precise control over the pore array in the multi-layered active material structure. This not only enhances the bonding force between the active material layers but also improves the overall structural stability of the electrode sheet by introducing additional channel structures. Furthermore, by controlling the gradient distribution of the porous structure of the electrode sheet, a high-porosity upper layer and a high-density lower layer can be achieved. This structure ensures both high energy density and fast-charging performance.
[0043] In the exemplary embodiments of this disclosure, the aperture channel array can be set up by laser etching technology. Laser etching technology, with its high precision and high resolution, can control the shape, size, position and depth of the channels, thereby ensuring that each channel can perform optimal ion transport.
[0044] In this disclosure, the appropriate diameters of the first, second, and third through-holes can achieve a balance between the high porosity structure of the upper layer and the high compaction density structure of the lower layer, which is beneficial for rapid ion transport and increased energy density. In some embodiments of this disclosure, the diameter of the first through-hole can be 10–50 μm; the diameter of the second through-hole can be 10–50 μm; and the diameter of the third through-hole can be 10–50 μm. For example, the diameter of the first through hole can be any value among 10μm, 15μm, 20μm, 25μm, 30μm, 35μm, 40μm, 45μm and 50μm or any value within the range of any two of the above values; the diameter of the second through hole can be any value among 10μm, 15μm, 20μm, 25μm, 30μm, 35μm, 40μm, 45μm and 50μm or any value within the range of any two of the above values; the diameter of the third through hole can be any value among 10μm, 15μm, 20μm, 25μm, 30μm, 35μm, 40μm, 45μm and 50μm or any value within the range of any two of the above values.
[0045] In some embodiments of this disclosure, the pore spacing L1 in the first active material layer satisfies the following relationship: 60≤L1≤100μm; the porosity of the first active material layer can be 5-25%. In this disclosure, if the pore spacing L1 in the first active material layer is too large, it may lead to a longer ion transport path between active material layers, increasing the resistance to ion transport; if the pore spacing L1 in the first active material layer is too small, it may lead to overly dense pores, and may also increase the difficulty and cost of the preparation process; if the porosity of the first active material layer is too large, it may lead to a weakening of the adhesion between the active material and the current collector, thereby reducing the overall structural stability of the electrode; if the porosity of the first active material layer is too small, it may restrict the penetration of the electrolyte, resulting in an increased volume change of the electrode during charging and discharging, increasing the internal stress of the battery. For example, the pore spacing L1 in the first active material layer can be any value of 60μm, 70μm, 80μm, 90μm and 100μm or any value within the range of any two of the above values; the porosity of the first active material layer can be any value of 5%, 10%, 15%, 20% and 25% or any value within the range of any two of the above values.
[0046] In some embodiments of this disclosure, the pore spacing L2 in the second active material layer satisfies the following relationship: 30 ≤ L2 < 60 μm, and the porosity of the second active material layer can be 30–55%. In this disclosure, if the pore spacing L2 in the second active material layer is too large, it may reduce the number of ion transport channels, decrease ion transport efficiency, and affect the fast-charging performance of the battery. If the pore spacing L2 in the second active material layer is too small, it may weaken the bonding force between the active material layers and may also affect the penetration of the electrolyte and the uniform distribution of ions. If the porosity of the second active material layer is too large, it may cause the active material layer structure to become loose, reduce the mechanical strength of the electrode, and may also affect the energy density of the battery. If the porosity of the second active material layer is too small, it may restrict the penetration of the electrolyte and the transport of ions, increase the internal resistance of the battery, and reduce the fast-charging performance and cycle life of the battery. For example, the pore spacing L2 in the second active material layer can be any value of 30μm, 40μm, 45μm, 50μm and 60μm or any value within the range of any two of the above values; the porosity of the second active material layer can be any value of 30%, 35%, 40%, 45% and 55% or any value within the range of any two of the above values.
[0047] In some embodiments of this disclosure, the pore spacing L3 in the third active material layer satisfies the following relationship: 10 ≤ L3 < 30 μm, and the porosity of the third active material layer can be 70-90%. In this disclosure, if the pore spacing L3 in the third active material layer is too large, it may reduce the number of ion transport channels, significantly reduce ion transport efficiency, and affect the fast-charging performance of the battery. If the pore spacing L3 in the third active material layer is too small, it may increase the flow resistance of the electrolyte within the pores, and may also affect the uniform distribution of the active material, reducing the overall performance of the battery. If the porosity of the third active material layer is too large, it may reduce the content of active material, thereby reducing the energy density of the battery. If the porosity of the third active material layer is too small, it may restrict the penetration of the electrolyte and the transport of ions, increase the internal resistance of the battery, and lead to a significant decrease in the fast-charging performance and cycle life of the battery, while also potentially affecting the structural stability of the battery. For example, the pore spacing L2 in the third active material layer can be any value of 10μm, 15μm, 20μm, 25μm and 29μm or any value within the range of any two of the above values; the porosity of the third active material layer can be any value of 70%, 75%, 80%, 85% and 90% or any value within the range of any two of the above values.
[0048] In some embodiments, the thickness of the first active material layer can be 30–70 μm; the thickness of the second active material layer can be 110–250 μm; and the thickness of the third active material layer can be 30–70 μm. Exemplarily, the thickness of the first active material layer can be any value selected from 30 μm, 40 μm, 50 μm, 60 μm, and 70 μm, or any value within the range formed by any two of the above values; the thickness of the second active material layer can be any value selected from 110 μm, 150 μm, 180 μm, 200 μm, and 250 μm, or any value within the range formed by any two of the above values; and the thickness of the third active material layer can be any value selected from 30 μm, 40 μm, 50 μm, 60 μm, and 70 μm, or any value within the range formed by any two of the above values.
[0049] In some embodiments, the first active material layer may include a first active material, which may be artificial graphite; and / or, the second active material layer may include a second active material, which may be artificial graphite; and / or, the third active material layer may include a third active material, which may include natural graphite and / or hard carbon. In this disclosure, placing artificial graphite in the bottom and intermediate layers provides good adhesion, sealing, conductivity, and mechanical strength. The choice of the surface material requires a trade-off based on the specific application scenario. If chemical stability and corrosion resistance are considered, natural graphite can be chosen; if high porosity and ion transport performance are required, hard carbon can be chosen. However, regardless of the material chosen as the surface layer, it is necessary to ensure good compatibility and adhesion between it and the bottom and intermediate layers.
[0050] In some embodiments of this disclosure, the pore channel array is distributed in a vertical array on the surface of the third active material layer; or, the pore channel array is distributed in a ring array on the surface of the third active material layer. In this disclosure, a vertical array distribution of the pore channel array on the surface of the third active material layer means that the pore channels are arranged in a direction perpendicular to the surface of the three active material layers; a ring array distribution of the pore channel array on the surface of the third active material layer means that the pore channels are arranged in a ring or concentric circles on the surface of the three active material layers.
[0051] In some embodiments of this disclosure, the negative electrode further includes a protective layer disposed on the surface of the third active material layer away from the second active material layer. By applying a protective layer to the surface of the third active material layer away from the second active material layer, this disclosure provides additional ion conduction paths and / or mechanical protection, thereby enhancing the overall performance and stability of the electrode.
[0052] Optionally, the thickness of the protective layer is 30–70 μm; and / or, the protective layer may include a solid electrolyte, wherein the solid electrolyte includes at least one of a sulfide electrolyte, an oxide electrolyte, a polymer electrolyte, and a ceramic electrolyte.
[0053] A second aspect of this disclosure provides a battery assembly including a negative electrode sheet, wherein the negative electrode sheet is the aforementioned negative electrode sheet.
[0054] A third aspect of this disclosure provides a battery comprising a negative electrode plate, wherein the negative electrode plate is the negative electrode plate described above.
[0055] A fourth aspect of this disclosure provides an electrical device comprising a battery, wherein the battery is the battery described above.
[0056] In some embodiments of this application, the battery further includes a positive electrode, an electrolyte, and a separator. That is, the battery includes a positive electrode, a negative electrode, an electrolyte, and a separator.
[0057] In this embodiment, the materials and structures of the positive electrode current collector, the conductive agent and the binder in the positive electrode active material layer are not limited, and the positive electrode structure and composition known in the art that can be used in secondary batteries can be selected.
[0058] In this embodiment, the specific material or type of the separator is not limited, and any separator known in the art that can be used in secondary batteries can be selected.
[0059] It should also be noted that the battery in this application does not limit the specific material or type of electrolyte. Any components and types known in the art that can be used in secondary batteries can be selected, as long as the purpose of this application can be achieved.
[0060] Since the battery provided in this application adopts all the technical solutions of the above embodiments, it has at least all the beneficial effects brought about by the technical solutions of the above embodiments, and will not be described in detail here.
[0061] The present application will be described in detail below with reference to the accompanying drawings and examples. However, the implementation and protection of the present application are not limited thereto. The following embodiments are only some embodiments of the present application and are not intended to limit the present application.
[0062] The present disclosure is further described in detail below through examples. All raw materials used in the examples are commercially available.
[0063] Example 1
[0064] In this embodiment, the coating structure of the negative electrode sheet includes, from the inside out, a first negative electrode active material layer, a second negative electrode active material layer, a third negative electrode active material layer, and a protective layer. The negative electrode active material in the first negative electrode active material layer includes artificial graphite, the negative electrode active material in the second negative electrode active material layer includes artificial graphite, the negative electrode active material in the third negative electrode active material layer includes hard carbon, and the protective layer is a solid electrolyte layer.
[0065] (1) Preparation of composite negative electrode with hierarchical structure
[0066] Styrene-butadiene latex and sodium carboxymethyl cellulose were selected as binders, conductive carbon black or carbon nanotubes as conductive agents, and deionized water as a dispersion solution. The first composite negative electrode slurry was prepared by mixing artificial graphite, binder, and conductive agent, with a mass ratio of 82.4%:12%:5.6% and a coating weight of 120 g / m². 2 Styrene-butadiene latex and sodium carboxymethyl cellulose were selected as binders, conductive carbon black or carbon nanotubes as conductive agents, and deionized water as a dispersion solution. A second composite negative electrode slurry was prepared by mixing artificial graphite, binder, and conductive agent, with a mass ratio of 96.4%:2.2%:1.4%; its coating weight per unit area was 242 g / m². 2 Styrene-butadiene latex and sodium carboxymethyl cellulose were selected as binders, conductive carbon black or carbon nanotubes as conductive agents, and deionized water as the dispersion solution. A third composite negative electrode slurry was prepared by mixing hard carbon, binder, and conductive agent, with a mass ratio of 82.4%:12%:5.6%; its coating weight per unit area was 120 g / m². 2 Using copper foil as the current collector, a first composite negative electrode slurry is uniformly coated onto the surface of the current collector, and then dried at 100°C for 60 min. Next, a second composite negative electrode slurry is uniformly coated onto the surface of the current collector already coated with the first composite negative electrode slurry, and then rapidly dried at 100°C for 60 min again. Finally, a third composite negative electrode slurry is uniformly coated onto the surface of the current collector already coated with the second composite negative electrode slurry, and then dried at 100°C for 60 min again, resulting in a negative electrode sheet coated with three layers of composite negative electrode slurry, wherein the thicknesses of the three layers of composite negative electrode slurry are 60 μm, 220 μm, and 60 μm, respectively. The electrode coated with the three layers of composite negative electrode slurry is then rolled and compacted to obtain a composite negative electrode with a layered structure.
[0067] (2) Fabrication of the pore channel array of the negative electrode sheet
[0068] A vertical channel array is precisely fabricated on a current collector coated with three layers of active material using laser etching technology. A spherical pattern is drawn and filled using the control software EZCAD 2.5.3 integrated with the fiber laser, and laser patterning is performed. The channel distribution exhibits a gradient distribution, as shown in this embodiment. Figure 2 As shown. The first active material layer has a pore spacing of 100 μm, a pore diameter of 50 μm, and a porosity of 10% of the first active material layer; the second active material layer has a pore spacing of 59 μm, a pore diameter of 50 μm, and a porosity of 40% of the second active material layer; the third active material layer has a pore spacing of 28 μm, a pore diameter of 50 μm, and a porosity of 80% of the third active material layer.
[0069] (3) Preparation of the protective layer of the negative electrode sheet
[0070] A protective layer is coated on the outermost layer of the negative electrode sheet with a pore channel array. This protective layer is made of ceramic solid electrolyte and includes the following raw materials in the following weight ratios: ceramic 95%; water-based adhesive (polyacrylic acid) 5%; solid content 20%; and the areal density of the coated active material is 8 g / m³. 2 The thickness is 30μm; the composite coated negative electrode sheet with protective layer is rolled, slit and punched to form a negative electrode sheet.
[0071] Example 2
[0072] The coating structure of the negative electrode sheet, the preparation method of the composite negative electrode with a hierarchical structure, and the preparation method of the protective layer of the negative electrode sheet in this embodiment are the same as in Embodiment 1. The difference is that the preparation method of the hole channel array of the negative electrode sheet in this embodiment includes: precisely fabricating an annular hole channel array on a current collector coated with three layers of active material using laser etching technology; drawing and filling a triangular pyramid pattern using the control software EZCAD2.5.3 provided with the fiber laser; and performing laser patterning processing. The hole channels are gradient distributed, as shown in this embodiment. Figure 3 As shown. The first active material layer has a pore spacing of 80 μm, a pore diameter of 30 μm, and a porosity of 13% of the first active material layer; the second active material layer has a pore spacing of 40 μm, a pore diameter of 30 μm, and a porosity of 46% of the second active material layer; the third active material layer has a pore spacing of 20 μm, a pore diameter of 30 μm, and a porosity of 83% of the third active material layer.
[0073] Example 3
[0074] The coating structure of the negative electrode sheet, the preparation method of the composite negative electrode with a hierarchical structure, and the preparation method of the protective layer of the negative electrode sheet in this embodiment are the same as in Embodiment 1. The difference is that the preparation method of the pore channel array of the negative electrode sheet in this embodiment includes: precisely fabricating an annular pore channel array on a current collector coated with three layers of active material using laser etching technology; drawing and filling a triangular pyramid pattern using the control software EZCAD2.5.3 provided with the fiber laser; performing laser patterning processing; the pore channels are gradient distributed; the pore spacing of the first active material layer is 60 μm, the pore diameter is 30 μm, and the porosity accounts for 22% of the first active material layer; the pore spacing of the second active material layer is 30 μm, the pore diameter is 30 μm, and the porosity accounts for 52% of the second active material layer; the pore spacing of the third active material layer is 10 μm, the pore diameter is 30 μm, and the porosity accounts for 89% of the third active material layer.
[0075] Comparative Example 1
[0076] The coating structure of the negative electrode sheet in this comparative example includes, from the inside out, a first negative electrode active material layer, a second negative electrode active material layer, a third negative electrode active material layer, and a protective layer. The negative electrode active material in the first negative electrode active material layer includes artificial graphite, the negative electrode active material in the second negative electrode active material layer includes artificial graphite, the negative electrode active material in the third negative electrode active material layer includes hard carbon, and the protective layer is a solid electrolyte layer.
[0077] The preparation method of the composite negative electrode in this comparative example includes:
[0078] Styrene-butadiene latex and sodium carboxymethyl cellulose were selected as binders, conductive carbon black or carbon nanotubes as conductive agents, and deionized water as a dispersion solution. The first composite negative electrode slurry was prepared by mixing artificial graphite, binder, and conductive agent, with a mass ratio of 82.4%:12%:5.6% and a coating weight of 120 g / m². 2 Styrene-butadiene latex and sodium carboxymethyl cellulose were selected as binders, conductive carbon black or carbon nanotubes as conductive agents, and deionized water as a dispersion solution. A second composite negative electrode slurry was prepared by mixing artificial graphite, binder, and conductive agent, with a mass ratio of 96.4%:2.2%:1.4%; its coating weight per unit area was 242 g / m². 2 Styrene-butadiene latex and sodium carboxymethyl cellulose were selected as binders, conductive carbon black or carbon nanotubes as conductive agents, and deionized water as the dispersion solution. A third composite negative electrode slurry was prepared by mixing hard carbon, binder, and conductive agent, with a mass ratio of 82.4%:12%:5.6%; its coating weight per unit area was 120 g / m². 2Using copper foil as the current collector, a first composite negative electrode slurry is uniformly coated onto the surface of the current collector, and then dried at 100°C for 60 min. Next, a second composite negative electrode slurry is uniformly coated onto the surface of the current collector already coated with the first composite negative electrode slurry, and then rapidly dried at 100°C for 60 min again. Finally, a third composite negative electrode slurry is uniformly coated onto the surface of the current collector already coated with the second composite negative electrode slurry, and then dried at 100°C for 60 min again, resulting in a negative electrode sheet coated with three layers of composite negative electrode slurry, wherein the thicknesses of the three layers of composite negative electrode slurry are 60 μm, 220 μm, and 60 μm, respectively. The electrode coated with the three layers of composite negative electrode slurry is then rolled and compacted to obtain a composite negative electrode with a layered structure.
[0079] A protective layer is coated on the outermost layer of the composite negative electrode with a hierarchical structure. This protective layer is made of ceramic solid electrolyte and includes the following raw materials in the following weight ratios: ceramic 95%; water-based adhesive (polyacrylic acid) 5%; solid content 20%; and the areal density of the coated active material is 8 g / m³. 2 The thickness is 5μm; the composite coated negative electrode sheet with protective layer is rolled, slit and punched to form a negative electrode sheet.
[0080] Test Example 1
[0081] Four sets of batteries were prepared by winding or stacking the negative electrode sheet, lithium iron phosphate positive electrode sheet, and separator obtained in Examples 1-3 and Comparative Example 4, followed by encapsulation, electrolyte injection, formation, secondary sealing, and sorting. The batteries were then subjected to capacity retention rate testing and fast charging performance testing.
[0082] The test procedure for capacity retention rate is as follows: The batteries prepared in the examples and comparative examples are placed in an environment of 25°C, and the batteries are fully charged at a rate of 1C, with a voltage range of 2.5V to 3.65V. Then, the batteries are discharged at 0.33C, and the discharge capacity is recorded as C0. After the batteries are cycled 200 times, the batteries are discharged at 0.33C again, and the discharge capacity is recorded as C1. The capacity retention rate of the batteries is η = C1 / C0. The results are recorded in Table 1.
[0083] Fast charging performance test: The batteries prepared in the examples and comparative examples were subjected to stepped charging at 25°C (2.8C, 2.4C, 2C, 1.6C, 1.0C, 0.6C, 0.33C). If the upper limit of the cutoff voltage (3.65V) was reached, the charging rate was skipped to the next step. The fast charging time from 0% to 80% SOC was recorded. If the required time was short and there was no lithium plating, the fast charging capability was good; if the required time was long and there was severe lithium plating, the fast charging capability was poor. The results are recorded in Table 1.
[0084] Table 1
[0085]
[0086] As shown in Table 1, the batteries prepared with the negative electrode sheets in Examples 1-3 of this disclosure exhibit significant improvements in capacity retention, fast charging time, and lithium plating compared to Comparative Example 1. In particular, the battery in Example 1 not only has a short fast charging time but also a high capacity retention and does not exhibit lithium plating, demonstrating excellent high energy density and fast charging capability. Although the batteries in Examples 2 and 3 are slightly inferior to Example 1 in various aspects, they are still significantly better than the comparative group. The annular pore array design in Examples 2 and 3, while potentially creating more complex flow paths, may also lead to less direct and efficient electrolyte flow, resulting in slightly lower capacity retention. In contrast, the vertical pores in Example 1 provide more direct channels, reducing electrolyte flow resistance and improving ion transport efficiency. The high porosity of Example 3 not only ensures high capacity retention but also optimizes fast charging performance, exhibiting advantages similar to Example 2. Therefore, it can be considered that the negative electrode sheet of this disclosure has a significant advantage in improving battery performance.
[0087] The above description is only a preferred embodiment of this disclosure. It should be noted that for those skilled in the art, several improvements and modifications can be made without departing from the principles of this disclosure, and these improvements and modifications should also be considered within the scope of protection of this disclosure.
Claims
1. A negative electrode sheet, characterized in that, The negative electrode sheet includes a negative current collector, a first active material layer disposed on at least one side surface of the negative current collector along the thickness direction, a second active material layer disposed on one side surface of the first active material layer away from the negative current collector, and a third active material layer disposed on one side surface of the second active material layer away from the first active material layer. The negative electrode sheet is provided with a pore channel array from the surface of the third active material layer to the surface of the negative electrode current collector; The aperture array includes a first through hole, a second through hole, and a third through hole; The first through hole penetrates the third active material layer, the second active material layer and the first active material layer; the second through hole penetrates the third active material layer and the second active material layer; and the third through hole penetrates the third active material layer.
2. The negative electrode sheet according to claim 1, characterized in that, The negative electrode sheet includes one or more of the following features (1) to (6): (1) The diameter of the first through hole is 10~50μm; (2) The diameter of the second through hole is 10~50μm; (3) The diameter of the third through hole is 10~50μm; (4) The pore spacing L1 in the first active material layer satisfies the following relationship: 60≤L1≤100μm; the porosity of the first active material layer is 5~25%; (5) The pore spacing L2 in the second active material layer satisfies the following relationship: 30≤L2<60μm, and the porosity of the second active material layer is 30~55%; (6) The pore spacing L3 in the third active material layer satisfies the following relationship: 10≤L3<30μm, and the porosity of the third active material layer is 70~90%.
3. The negative electrode sheet according to claim 1, characterized in that, The thickness of the first active material layer is 30~70μm; and / or, The thickness of the second active material layer is 110~250 μm; and / or, The thickness of the third active material layer is 30~70μm.
4. The negative electrode sheet according to claim 1, characterized in that, The first active material layer includes a first active material, which is artificial graphite; and / or, The second active material layer includes a second active material, which is artificial graphite; and / or, The third active material layer includes a third active material.
5. The negative electrode sheet according to claim 1, characterized in that, The pore channel array is vertically distributed on the surface of the third active material layer; or... The pore channel array is distributed in a ring array on the surface of the third active material layer.
6. The negative electrode sheet according to claim 1, characterized in that, The negative electrode sheet also includes a protective layer disposed on the surface of the third active material layer away from the second active material layer.
7. The negative electrode sheet according to claim 6, characterized in that, The thickness of the protective layer is 30~70μm.
8. A battery assembly, characterized in that, The battery assembly includes a negative electrode sheet, which is the negative electrode sheet according to any one of claims 1 to 7.
9. A battery, characterized in that, The battery includes a negative electrode sheet, which is the negative electrode sheet according to any one of claims 1 to 7.
10. An electrical appliance, characterized in that, The electrical device includes a battery, which is the battery described in claim 9.